Atmospheric Flow Fields: Theory, Numerical Methods and Software Tools - Grifoni, Roberta Cocci; Tascini, S.; Latini, G. (Bentham Science Publishers, 2012)
This e-book is a collection of chapters on practical and theoretical aspects of atmospheric flows over flat and complex terrain, with applications to air pollution and wind energy. It is divided into two main sections: the first section deals with atmospheric dynamics, and the second section explains the planetary boundary-layer parameterization that is a key issue for the definition of initial wind flow fields in meteorological and prognostic estimation of turbulence - "Ensemble Nowcasting" for short term prediction. The e-book is unique in that it features a combination of theoretical, analytical and numerical techniques, and tools where the techniques presented in the e-book are demonstrated and can be replicated by the reader. These practical tools can be used to easily test selected mathematical formulation or for performing a swift sensitivity analysis. The tools presented in this reference work focus primarily on mixing height evaluation, representative day identification and PBL characterization by elementary measurements evaluated at surface level. This e-book should be a valuable reference for readers interested in the meteorology of atmospheric wind flows.